Rule of experts : Egypt, techno-politics, modernity - Mitchell, Timothy, 1955- (Berkeley : University of California Press, 2002)
In a series of interrelated essays focused on twentieth-century Egypt, the author, a political theorist, provides an examination of the forms of reason, power and expertise that characterize contemporary politics.
I. Para-sites of capitalism. Can the mosquito speak? ; Principles true in every country ; The character of calculability -- II. Peasant studies. Invention and reinvention of the peasant ; Nobody listens to a poor man ; Heritage and violence -- III. Fixing the economy. Object of development ; Market's place ; Dreamland.
Parts of the text previously published.
Includes bibliographical references (pages 381-401) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Egypt -- Economic policy; Peasants -- Egypt -- History -- 20th century; Egypt -- Economic conditions -- 1919-1952.; Egypt -- Economic conditions -- 1952-; Egypt -- Politics and government -- 20th century; Egypt -- Economic policy; Paysannerie -- Égypte -- Histoire -- 20e siècle.; Égypte -- Politique économique.; Égypte -- Conditions économiques -- 1919-1952.; Égypte -- Conditions économiques -- 1952-; Égypte -- Politique et gouvernement -- 20e siècle.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; HISTORY -- Middle East -- General; Politics and government; Economic history; Economic policy; Peasants; Egypt; Wirtschaftspolitik; Moderne; Ägypten; Politieke situatie; Egypte; Paysannerie -- Égypte -- 20e siècle.; Égypte -- Conditions économiques -- 20e siècle.; Égypte -- Politique et gouvernement -- 20e siècle.; Since 1900; History